Treatment of osteonecrosis of the femoral head with free vascularized fibular grafting: results of 7.6-year follow-up - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2016)
Objective: The aim of this study was to determine long-term follow-up results of patients with femoral head osteonecrosis who were treated with free vascularized fibular grafting (FVFG). Methods: The results of 28 hips of 21 patients (16 male, 5 female) who underwent FVFG for treatment of osteonecrosis of the femoral head were retrospectively reviewed. Mean age of patients at time of surgery was 30.7 years (range: 15-53 years). Mean follow-up duration was 7.6 years (range: 5-9.2 years). Results: During follow-up, 1 patient died because of leukemia, and 1 patient was lost. The remaining 26 hips of 19 patients were evaluated. According to Ficat classification, at time of surgery, 17 hips were grade II, and 9 hips were grade III, 3 hips underwent total hip arthroplasty. Postoperative Harris Hip Score (HHS) in grade II disease was excellent in 12 patients, good in 3 patients, and fair in 1 patient. In grade III disease, 1 patient was excellent, 5 patients were good, and 1 patient was fair. There was a significant increase in HHS scores from preoperatively to postoperatively (61 +/- 9.7 vs 84 +/- 17.8, p<0.001). Conclusion: FVFG yields extremely good results, particularly in pre-collapse stages of the disease in young patients. The operation time does not markedly increase if the surgical team is knowledgeable of the procedure and the residual fibular defect of the donor site does not impair functions of daily living.
Keywords: Free vascularized fibular grafting; osteonecrosis of the femoral head; NONTRAUMATIC AVASCULAR NECROSIS; INTERTROCHANTERIC OSTEOTOMY; BONE-SCINTIGRAPHY; HIP